Developing reflective capacities in midwifery students: Enhancing learning through reflective writing. Issue 2 (April 2019) - Sweet, Linda; Bass, Janice; Sidebotham, Mary; Fenwick, Jennifer; Graham, Kristen
Abstract: Background: Practice-based or clinical placements are highly valued for linking theory to practice and enabling students to meet graduate outcomes and industry standards. Post-practicum, the period immediately following clinical experiences, is a time when students have an opportunity to share, compare and engage critically in considering how these experiences impact on their learning. Reflective practice has merit in facilitating this process. Aim: This project aimed to optimise the learning potential of practice-based experiences by enhancing midwifery students' capacity for reflective practice through writing. Methods: Design-based research was used to implement an educational intervention aimed at developing reflective practice skills and enhance reflective writing. The Bass Model of Holistic Reflection was introduced to promote the development of reflective capacity in midwifery students. Academics and midwifery students were provided with guidance and resources on how to apply the model to guide reflective writing. Students' written reflections completed before (n = 130) and after the introduction of the intervention (n = 96) were evaluated using a scoring framework designed to assess sequential development of reflective capacity. Findings: The pre-intervention scores ranked poorly as evidence of reflective capacity. All scores improved post-intervention. Conclusions: The introduction of a holistic structured model of reflection resulted in improved scores across all five components of reflective writing; self-awareness, sources of knowledge, reflection and critical reflection, evidence informed practice and critical thinking. While further work is required the results show that the implementation process and use of the Bass Model enables students to demonstrate their capacity to reflect-on-practice through their writing.